Biological risk assessment of heavy metals in sediments and health risk assessment in bivalve mollusks from Kaozhouyang Bay, South China. (August 2018) - Wang, Xu-Nuo; Gu, Yang-Guang; Wang, Zeng-Huan; Ke, Chang-Liang; Mo, Meng-Song
Abstract: The concentrations of heavy metals (Cd, Pb, Cr, Ni, Cu, Zn, Hg and As) in surface sediments and bivalve mollusks in Kaozhouyang Bay were investigated. A biological risk analysis of the sediments indicated that ten sites (about 76.92% of the total number of sites) had a 21% incidence probability of toxicity. A health risk analysis of the bivalve mollusks indicated that Cu and As posed low risks to consumer health. On the basis of the target hazard quotient (THQ), adverse effects may occur based on total THQ (TTHQ). The highest TTHQ was found in the species, Ostrea rivularis, which had the highest capacity for the bioaccumulation (factor > 38) of Cd. Highlights: Bivalves had the highest capacity to bioaccumulation of Cd. The sediments had a 21% probability of toxicity. Adverse effects of consumption bivalves may happen to human health.